4CPS-155 A new multidisciplinary model with the clinical pharmacist for medication reconciliation in the patient with advanced renal disease. (March 2019) - Masucci, S; Soragna, G; Cerutti, E; Riba, M; Azzolina, MC; Vitale, C; Gasco, A
Abstract : Background: Most of the patients with advanced chronic kidney disease (ACKD) are fragile due to multimorbidity and associated polypharmacy. For this kind of population, polypharmacy and potentially inappropriate prescribing are common problems that impact both on patient compliance and on drugs cost for the National Health System (NHS). For therapy with high pill-burden medication reconciliation (MR), supported by Information and Communication Technology's (ICT) instrument, is one of the most effective tools in preventing over/under/mis-prescription and drug interaction (DI), and the clinical pharmacist is the suitable figure to support the clinician in promoting the appropriateness of therapies in the transition of care. Purpose: The aim was to estimate compliance and the economic impact of a multidisciplinary clinical-pharmacist-led MR process in patients with ACKD. Material and methods: Selection and implementation of ICT tool; identification of mistaken prescription with indicators of appropriateness, such as START/STOPP and Beers criteria; proposal and evaluation of new therapies with the nephrologist; and estimation of therapies costs pre- and post-MR. Results: The identified ICT tool was the acknowledged platform NavFarma Suite, the same as used in two other regional projects with the purpose of creating a path between admission and discharge therapy. MR was conducted in 92 patients. The clinical pharmacist identified 265 DI, five classified as contraindicated and 260 as major, with a level of evidence equal to 52% excellent, 16% good and 32% discrete. 3.75% of therapies analysed were considered inappropriate. Cost analysis: the average cost of a single treatment for the patient was €704 charged to the NHS and €102 charged to the patient. The MR allowed a cost reduction of 4% for the NHS and of 37% for the patient. Conclusion: The project demonstrates that MR is one of the most appropriate methodologies to correct prescription errors, improve patient compliance and carry out a more effective model for pharmaceutical expenditure management. Technology and multidisciplinary summarises more suitable the innovation of the proposed model, in which a new figure, the clinical pharmacist, integrates the medical and nursing team by bringing his contribution in terms of pharmacological and pharmacokinetic knowledge and stimulates the critical evaluation of the therapeutic choices and of the data processed through the use of an accurate ICT tool. References and/or acknowledgements: No conflict of interest.